2015
DOI: 10.1002/brb3.328
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the ~20‐Hz motor‐cortex rhythm to passive movement and tactile stimulation

Abstract: BackgroundIntegration of afferent somatosensory input with motor-cortex output is essential for accurate movements. Prior studies have shown that tactile input modulates motor-cortex excitability, which is reflected in the reactivity of the ∽20-Hz motor-cortex rhythm. ∽20-Hz rebound is connected to inhibition or deactivation of motor cortex whereas suppression has been associated with increased motor cortex activity. Although tactile sense carries important information for controlling voluntary actions, propri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 70 publications
3
39
0
Order By: Relevance
“…The 20-Hz cortical rhythm measured in MEG is initially decreased (suppression; reflecting an activated M1) and subsequently increased (rebound; reflecting inhibited M1) and represents the functional state of M1. 68,76 Combined MEG and MRS showed a positive correlation between 20-Hz rebound amplitude and the concentration of the inhibitory neurotransmitter GABA, indicating the rebound period represents GABAergic inhibition in M1. 27 MEG studies reported a significantly shorter rebound duration of 20-Hz rhythm in both hemispheres, 39 and weaker rebound amplitude and re-activity of 20-Hz rhythm in the hemisphere contralateral to the affected side, 40 indicating M1 disinhibition in CRPS.…”
Section: Evidence For Altered Icf And/or Inhibition In Chronic Painmentioning
confidence: 99%
“…The 20-Hz cortical rhythm measured in MEG is initially decreased (suppression; reflecting an activated M1) and subsequently increased (rebound; reflecting inhibited M1) and represents the functional state of M1. 68,76 Combined MEG and MRS showed a positive correlation between 20-Hz rebound amplitude and the concentration of the inhibitory neurotransmitter GABA, indicating the rebound period represents GABAergic inhibition in M1. 27 MEG studies reported a significantly shorter rebound duration of 20-Hz rhythm in both hemispheres, 39 and weaker rebound amplitude and re-activity of 20-Hz rhythm in the hemisphere contralateral to the affected side, 40 indicating M1 disinhibition in CRPS.…”
Section: Evidence For Altered Icf And/or Inhibition In Chronic Painmentioning
confidence: 99%
“…During the MEG measurements, the subjects were either sitting or in supine position (4 patients at T 0 ) and instructed to relax, not to pay attention to the finger lift and to avoid excessive blinking. 13 Four indicator coils, 3 anatomical landmarks (right and left preauricular points and nasion) and 50 to 100 additional points on the head surface were used for co-registration.…”
Section: Meg Recordingsmentioning
confidence: 99%
“…12 Accordingly, our previous study in healthy subjects indicated that proprioceptive input strongly modulates the ~20-Hz motor cortex rhythm, causing an initial suppression followed by a strong and robust rebound. 13 Prior studies have suggested that the ~20-Hz rebound reflects deactivation or inhibition of the motor cortex. [14][15][16][17] Moreover, a combined magnetiencephalography (MEG) and magnetic resonance spectroscopy study showed that the ~20-Hz rebound strength is associated with the concentration of the inhibitory neurotransmitter GABA (γ-aminobutyric acid).…”
Section: Introductionmentioning
confidence: 99%
“…beta rhythm | magnetoencephalography | computational modeling | sensorimotor processing | Parkinson's disease B eta band rhythms (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) are a commonly observed activity pattern in the brain. They are found with magnetoencephalography (MEG) (1)(2)(3)(4), EEG (5,6), and local field potential (LFP) recordings from neocortex (7)(8)(9) and are preserved across species (10). Local beta oscillations and their coordination between regions are implicated in numerous functions, including sensory perception, selective attention, and motor planning and initiation (2,3,6,7,9,(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…However, burst-like or intermittent periods of high beta power occurring stochastically within the time-averaged period could appear as continuous rhythms in averaged spectrograms, despite not ever actually being sustained. Several recent studies have shown that in nonaveraged data beta oscillations often emerge transiently, typically lasting <150 ms (2,4,(30)(31)(32).…”
mentioning
confidence: 99%